Microwave Applications in Chemical Engineering - Huang, Kama; Tao, Junwu; Zhu, Huacheng (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue comprises 9 research papers on the application of microwaves in chemical engineering, covering the basic research into the optimization design of microwave reaction equipment as well as methods to improve microwave heating uniformity. Also included are the practical application of microwave-assisted processing in chemical engineering in the extraction of traditional Chinese medicine and essential oils from plant materials; the treatment of carbon fiber-reinforced polymer waste; and the drying treatment of drill cuttings and Zhaotong lignite. These 9 papers together represent unique and valuable references in the research of microwave technology.